The Palgrave Handbook of Contemporary Irish Theatre and Performance
XXXIII, 866 p. 21 illus.
Keywords: This Handbook offers a multiform sweep of theoretical, historical, practical and personal glimpses into a landscape roughly characterised as contemporary Irish theatre and performance. Bringing together a spectrum of voices and sensibilities in each of its four sections — Histories, Close-ups, Interfaces, and Reflections — it casts its gaze back across the past sixty years or so to recall, analyse, and assess the recent legacy of theatre and performance on this island. While offering information, overviews and reflections of current thought across its chapters, this book will serve most handily as food for thought and a springboard for curiosity. Offering something different in its mix of themes and perspectives, so that previously unexamined surfaces might come to light individually and in conjunction with other essays, it is a wide-ranging and indispensable resource in Irish theatre studies.